Xerostomia induced by radiotherapy: an overview of the physiopathology, clinical evidence, and management of the oral damage - Pinna R; Campus G; Cumbo E; Mura I; Milia E (Dove Medical Press, 2015)
Roberto Pinna,1 Guglielmo Campus,2 Enzo Cumbo,3 Ida Mura,1 Egle Milia2 1Department of Biomedical Science, 2Department of Surgery, Microsurgery and Medicine, University of Sassari, Sassari, 3Department of Dental Science, University of Palermo, Palermo, Italy Background: The irradiation of head and neck cancer (HNC) often causes damage to the salivary glands. The resulting salivary gland hypofunction and xerostomia seriously reduce the patient’s quality of life. Purpose: To analyze the literature of actual management strategies for radiation-induced hypofunction and xerostomia in HNC patients. Methods: MEDLINE/PubMed and the Cochrane Library databases were electronically evaluated for articles published from January 1, 1970, to June 30, 2013. Two reviewers independently screened and included papers according to the predefined selection criteria. Results: Sixty-one articles met the inclusion criteria. The systematic review of the literature suggests that the most suitable methods for managing the clinical and pathophysiological consequences of HNC radiotherapy might be the pharmacological approach, for example, through the use of cholinergic agonists when residual secretory capacity is still present, and the use of salivary substitutes. In addition, a modified diet and the patient’s motivation to enhance oral hygiene can lead to a significant improvement. Conclusion: Radiation-induced xerostomia could be considered a multifactorial disease. It could depend on the type of cancer treatment and the cumulative radiation dose to the gland tissue. A preventive approach and the correct treatment of the particular radiotherapeutic patient can help to improve the condition of xerostomia. Keywords: radiation-induced xerostomia, salivary gland hypofunction, management strategies